Isolation and Characterization of Chemical Constituents from the Roots of Carissa carandas - Hegde, Karunakar; P. Thakker, Shalin; B. Joshi, Arun (Asian Journal of Chemistry, 2010)
In the present study, three triterpenoids were isolated and characterized from petroleum ether extract of the roots of Carissa carandas. The compounds ursolic acid, lupa-12,20(29)-dien-3β,28-diol and urs-12-ene- 3β,22β-diol were reported for the first time in this plant.